Development of Student Worksheet for Sound Waves Based on Project Based Learning Model to Improve Students' Science Literacy - Febiyanti Ansumarwaty; Jannatin 'Ardhuha; Hikmawati Hikmawati; Muh. Makhrus (Jurnal Penelitian Pendidikan IPA, 2023)
Research and Development (R&D) research is included in this study using the 4D model developed by Thiagarajan. The product developed student worksheetound waves. Data collection techniques used validation sheets, teacher learning implementation observation sheets, student response questionnaires and test instruments. This product was assessed for validity by three expert validators who are physics lecturers and three practitioner validators who are physics subject teachers. Its validity was obtained from the assessment results of expert and practitioner validators, which reached 91.67% and 94.70% respectively, indicating that the product was very valid. In addition, the reliability value also met the standard with an average of above 75%. Therefore, it can be said that this product is feasible to use. The practicality of this product was evaluated through observation sheets by teachers and questionnaires filled out by students related to the learning carried out. The assessment results show that this product is very practical, with the implementation sheet by the teacher reaching 94.56% and the response of students reaching 89.54%. In addition to validity and practicality, the effectiveness of this product was also assessed. The limited trial was conducted by measuring the increase in pretest and posttest scores using the N-Gain test. The analysis results show that this product is quite effective, with the acquisition of the N-Gain test for students' science literacy of 0.69, which is in the medium category. Based on the evaluation results, it can be concluded that the sound waves student worksheetroduced is a feasible product, very practical, and quite effective in improving students' science literacy.